Guilt is effectively induced by a written auto-biographical essay but not reduced by experimental pain - Schär, Selina; Vehlen, Antonia; Ebneter, Julia; Schicktanz, Nathalie; de Quervain, Dominique J. F.; Wittmann, Lutz; Götzmann, Lutz; grosse Holtforth, Martin; Protic, Sonja; Wettstein, Alexander; Egloff, Niklaus; Streitberger, Konrad; et al. (Frontiers in Behavioral Neuroscience, 2022)
Introduction The aim of the present study was (1) to validate the method of guilt-induction by means of a written auto-biographical essay and (2) to test whether experimental pain is apt to alleviate the mental burden of guilt, a concept receiving support from both empirical research and clinical observation. Methods Three independent groups of healthy male participants were recruited. Group allocation was not randomized but within group pain/sham administration was counterbalanced over the two test-days. Groups were tested in the following consecutive order: Group A: guilt induction, heat-pain/sham, N = 59; Group B: guilt induction, cold-pressure-pain/sham, N = 43; Group C: emotionally neutral induction, heat-pain/sham, N = 39. Guilt was induced on both test-days in group A and B before pain/sham administration. Visual analog scale (VAS) guilt ratings immediately after pain/sham stimulation served as the primary outcome. In a control group C the identical heat-pain experiment was performed like in group A but a neutral emotional state was induced. Results A consistently strong overall effect of guilt-induction (heat-pain: p < 0.001, effect size r = 0.71; CPT-pain p < 0.001, r = 0.67) was found when compared to the control-condition (p = 0.25, r = 0.08). As expected, heat- and cold-pressure-stimuli were highly painful in all groups (p < 0.0001, r = 0.89). However, previous research supporting the hypothesis that pain is apt to reduce guilt was not replicated. Conclusion Although guilt-induction was highly effective on both test-days no impact of pain on behavioral guilt-ratings in healthy individuals could be identified. Guilt induction per se did not depend on the order of testing. The result questions previous experimental work on the impact of pain on moral emotions.